Unexpected Sole Enol‐Form Emission of 2‐(2′‐Hydroxyphenyl)oxazoles for Highly Efficient Deep‐Blue‐Emitting Organic Electroluminescent Devices. (12th January 2017) - Li, Bijin; Tang, Guoqiang; Zhou, Linsen; Wu, Di; Lan, Jingbo; Zhou, Liang; Lu, Zhiyun; You, Jingsong
Abstract : Considerable efforts have been devoted to the development of highly efficient blue light‐emitting materials. However, deep‐blue fluorescence materials that can satisfy the Commission Internationale de l'Eclairage (CIE) coordinates of (0.14, 0.08) of the National Television System Committee (NTSC) standard blue and, moreover, possess a high external quantum efficiency (EQE) over 5%, remain scarce. Here, the unusual luminescence properties of triphenylamine‐bearing 2‐(2′‐hydroxyphenyl)oxazoles (3a–3c ) and their applications in organic light‐emitting diodes (OLEDs) are reported as highly efficient deep‐blue emitters. The3a ‐based device exhibits a high spectral stability and an excellent color purity with a narrow full‐width at half‐maximum of 53 nm and the CIE coordinates of (0.15, 0.08), which is very close to the NTSC standard blue. The exciton utilization of the device closes to 100%, exceeding the theoretical limit of 25% in conventional fluorescent OLEDs. Experimental data and theoretical calculations demonstrate that3a possesses a highly hybridized local and charge‐transfer excited state character. In OLEDs, 3a exhibits a maximum luminance of 9054 cd m −2 and an EQE up to 7.1%, which is the first example of highly efficient blue OLEDs based on the sole enol‐form emission of 2‐(2′‐hydroxyphenyl)azoles. Abstract : The unusual sole enol‐form emission of 2‐(2′‐hydroxyphenyl)oxazoles and their application in organic light‐emitting diodes (OLEDs) have been investigated. The device exhibits an excellent color purity, a spectral stability, and an external quantum efficiency up to 7.1%, which is the first example of highly efficient blue OLEDs based on the sole enol‐form emission of 2‐(2′‐hydroxyphenyl)azoles.